권리보호를 위한 기록정보서비스 - 설문원; Moon-won Seol (Journal of Records Management & Archives Society of Korea, 2025)
Archival information services supporting rights protection have garnered less academic attention than services for educational and academic support services. The study proposes a comprehensive framework encompassing institutional, practical, and theoretical elements essential for establishing a rights-based paradigm in archival information services. First, the study examines the theoretical foundations of records as instruments for the exercise or protection of rights. Through the analysis of rights conceptualization and records agency, the study demonstrates that records function as active agents in user relationships. Second, its historical investigation traces the evolution of rights documentation, examining their function in ancient and medieval Western societies, and analyzes the emergence of 'feudists' in 18th-century France as precursors to modern archival professionals. Third, it further examines the transformation of archival services from protecting the rights of the ruling class to providing universal access for citizens in the modern era. Based on this historical and theoretical analysis, the study proposes a contemporary framework for rights-based archival information services in democratic societies. This framework encompasses three key dimensions: i) institutionalization of legal access to ensure universal service provision, ii) implementation of intellectual and physical access through service practices, and iii) development of mechanisms for reconciling competing rights claims. 권리보호를 위한 기록정보서비스는 교육이나 학술지원을 위한 서비스에 비해 학술적으로는 별로 주목받지 못해왔다 이는 실제 국내 서비스 . 현장에서 확인할 수 있는 기록정보 요구와는 거리가 있는 현상이다. 이 연구는 권리 패러다임의 기록정보서비스 체제를 구축하기 위하여 고려할 제도, 실무, 이론 측면의 요소들을 제안하기 위한 것이다. 이를 위하여 이 연구에서는 첫째, 기록은 어떻게 권리 행사나 보호의 도구가 될 수 있는지 이론적으로 살펴보았다. 권리의 개념과 기록의 행위성을 중심으로 분석하여, 이용자와의 관계 속에서 기록 자체가 행위성을 갖는 주체가 될 수 있음을 정리하였다. 둘째, 기록관리역사에서 권리보호라는 역할은 어떻게 존재했는지 파악하였다. 이를 위해 서양 고대와 중세의 권리 문서와 그 역할, 특히 18세기에 프랑스에서 활약했던 봉건학자(feudists)의 역할을 추적함으로써 권리보호를 위한 전문적 기록관리의 전통을 확인하였다. 셋째, 근대 이후 지배층의 권리보호에서 시민 일반을 위한 보편적 서비스로 이행하는 과정을 조사하여 현대 기록정보서비스 제도의 특징을 도출하였다. 마지막으로, 선행 조사를 토대로 현대민주주의 사회에서 권리 기반의 기록정보서비스 체제는 어떻게 구축되어야 하는지 제안하였다. 여기에는 i) 보편적 서비스를 위한 제도화를 통한 법적 접근권의 확보, ii) 서비스 실무를 통한 지적, 물리적 접근권의 확보, 그리고 iii) 경합하는 권리 조정을 위한 정책, 실무, 윤리적 지향 등을 포함하였다.